2000
DOI: 10.1053/jvet.2000.17836
|View full text |Cite
|
Sign up to set email alerts
|

Use of Pelvic Flexure Biopsies to Predict Survival After Large Colon Torsion in Horses

Abstract: Use of frozen colonic tissue sections is a rapid, reliable, and relatively inexpensive method for assessing morphologic damage associated with large colon torsion during surgery. Intraoperative evaluation of pelvic flexure biopsies can aid in the prediction of survival and guide surgical judgment as to the need for colonic resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
53
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 13 publications
5
53
0
3
Order By: Relevance
“…Champault et al (1983) found colonic torsion accounted for 12% of 497 cases of colon obstruction in humans. The suggested aetiopathologies in horses and primates included dietary factors, infl ammatory bowel disease and Hirschprung-related enterocolitides (Farrell 1967;Foerner 1982;Champault et al 1983;Specht and Colahan 1988;Lashner et al 1989;Fincham et al 1992;Carberry and Flanders 1993;Sarioglu et al 1997;van Hoogmoed et al 2000). In the equine, the colon may be predisposed to torsion as it is relatively long and has a short mesenteric attachment (Carberry and Flanders 1993).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Champault et al (1983) found colonic torsion accounted for 12% of 497 cases of colon obstruction in humans. The suggested aetiopathologies in horses and primates included dietary factors, infl ammatory bowel disease and Hirschprung-related enterocolitides (Farrell 1967;Foerner 1982;Champault et al 1983;Specht and Colahan 1988;Lashner et al 1989;Fincham et al 1992;Carberry and Flanders 1993;Sarioglu et al 1997;van Hoogmoed et al 2000). In the equine, the colon may be predisposed to torsion as it is relatively long and has a short mesenteric attachment (Carberry and Flanders 1993).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that megacolon remained 3.5 months post-operatively lends weight to the suspicion that a degree of colonic dysfunction existed in this dog. Colonic biopsies have been used in humans and horses to confi rm the aetiopathogenesis of, and to predict survival following, large bowel torsion (Sarioglu et al 1997;van Hoogmoed et al 2000). The collection of full thickness colonic biopsies for histopathology was discussed at the time of surgical correction of the colonic torsion but was not performed.…”
Section: Discussionmentioning
confidence: 99%
“…Severe mucosal injury likely compromises the proliferative cell population that resides within the glandular crypts. A study 5 has shown that intestinal ischemic injury that denudes > 50% of the glandular epithelium, such as occurs with large colon volvulus, is associated with a poor prognosis for survival. However, research to explore this proliferative compartment of the intestinal mucosa in further detail has been lacking because, until recently, the technology to distinctly identify unique cell types did not exist.…”
mentioning
confidence: 99%
“…In the large intestine, loss of epithelium extending beyond 50% of the crypt is associated with poor outcome in colic cases (Van Hoogmoed et al . ). This poor outcome is likely to be associated with loss of the progenitor pool of cells as has been recently proposed (Gonzalez et al .…”
mentioning
confidence: 99%